Using Indirect Speech Acts and Their Impacts on Creating a Conducive Workplace Environment - Fatimah Hidayahni Amin; Seny Luhriyani; Sri Puji Rahayu; Muhammad Syukri; Rahma Melati Amir (Universitas Islam Ahmad Dahlan (UIAD), 2024)
Communication at the workplace requires meaningful understanding because it affects the work relationship as well as the work atmosphere. Hence, expressions used to generate such conditions are supposed to embody a conducive environment. This research aimed to determine the types of indirect speech acts and their language functions. This study used a qualitative research with a descriptive design to depict the phenomenon. The subjects were three employees at PT. Bosowa Berlian Motor Makassar, who were chosen purposively considering their availability and their readiness during the data collection. The data were collected by using observation with audio recordings and the researchers themselves as the non-participant observers. The results of this study showed that there were five types of indirect speech acts and there were certain language functions practiced by the employees, they are: emphasizing and instructing (assertive type), telling a condition and commanding what to do (directive type), directing and checking for the appropriate work (commissive type), complaining and giving subtle offense (expressive type), and responding, telling information and encouraging (declarative type). All types and their functions revealed and occurred to meet the need of creating a conducive environment in the workplace. The five types represent the traits of being assertive, directive, trusted, expressive, and declarative along with their use of language functions. These traits bear positive and good atmosphere in the workplace. Thus, with the conducive working environment, the employees can undertake their tasks well and focus on reaching the target in the workplace.